2021
DOI: 10.1177/01455613211007947
|View full text |Cite
|
Sign up to set email alerts
|

Neurilemmoma of the Nasal Cavity and Paranasal Sinuses

Abstract: Objectives: Neurilemmoma in the nasal cavity and paranasal sinuses is very rare. The study aimed to improve the understanding of neurilemmoma in the nasal cavity and paranasal sinuses. Materials and Methods: The clinical data of 10 patients with neurilemmoma in the nasal cavity and paranasal sinuses treated from January 2014 to June 2019 in our hospital were retrospectively studied. Results: There were 6 females and 4 males patients in our study. The mean age was 49.5 years (range 37-77 years), and the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The search yielded 52 studies and a total of 71 patients, including this reported case. 1,2,7,9 -11,13 -58…”
Section: Discussionmentioning
confidence: 99%
“…The search yielded 52 studies and a total of 71 patients, including this reported case. 1,2,7,9 -11,13 -58…”
Section: Discussionmentioning
confidence: 99%